2013
DOI: 10.1557/jmr.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and characterization of nanostructured Cu2O thin-film for potential photovoltaic applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…Du and Wang [12] also reported the preparation of p-Cu 2 O/n-Si heteroepitaxial junction by DC magnetron reactive sputtering he observes a rather large irreversible lateral PV effect revealed from the large output voltage and the high linearity of the device output. Finally, Gupta et al [13] studied the electrical properties of Cu 2 O/ Si junction prepared by using photo-assisted metal-organic chemical vapor deposition method his study reveal the lowest reported leakage current density at zero bias of 1.5 9 10 -12 A/cm which is a major indicator of low bulk and surface recombination and indicates the potential of Cu 2 O as a PV material. In addition, Cu 2 O/p-Si Schottky heterojunction was also achieved by the pulse laser deposition and chemical deposition [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Du and Wang [12] also reported the preparation of p-Cu 2 O/n-Si heteroepitaxial junction by DC magnetron reactive sputtering he observes a rather large irreversible lateral PV effect revealed from the large output voltage and the high linearity of the device output. Finally, Gupta et al [13] studied the electrical properties of Cu 2 O/ Si junction prepared by using photo-assisted metal-organic chemical vapor deposition method his study reveal the lowest reported leakage current density at zero bias of 1.5 9 10 -12 A/cm which is a major indicator of low bulk and surface recombination and indicates the potential of Cu 2 O as a PV material. In addition, Cu 2 O/p-Si Schottky heterojunction was also achieved by the pulse laser deposition and chemical deposition [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in 0D [9], 1D [10] and 2D [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] material fabrication technologies have enabled various forms of nanoscale materials, which can be used as nanostructured anodes to accommodate the large volume changes during cycling. For example, silicon nanowire anodes were reported to retain high capacity during several charge-discharge cycles in spite of an initial volume change of 400% [27], while bulk silicon loses more than 80% of its capacity in less than 10 cycles due to pulverization [28].…”
Section: Importance Of Developing Platforms Enabling In-situ Electrocmentioning
confidence: 99%
“…Advances in 0D [32], 1D [33] and 2D [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] material fabrication technologies have enabled various forms of nanoscale materials, which increased the needs of in-situ ETEM studies through the closed-type approach, i.e. windowed gas cells.…”
Section: Windowed Gas Cells (Closed Type Etem)mentioning
confidence: 99%